Nanoindentation Response analysis of Thin Film Substrates-I: Strain Gradient-Divergence Approach - Kanders U. (Latvian Journal of Physics and Technical Sciences, 2017)
Nanoindentation is a widely-used method for sensitive exploration of the mechanical properties of micromechanical systems. We derive a simple empirical analysis technique to extract stress-strain field (SSF) gradient and divergence representations from nanoindentation data sets. Using this approach, local SSF gradients and structural heterogeneities can be discovered to obtain more detail about the sample’s microstructure, thus enhancing the analytic capacity of the nanoindentation technique. We demonstrate the application of the SSF gradient-divergence analysis approach to nanoindentation measurements of bulk silicon.